ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI MINAT SISWA MENERUSKAN KULIAH DI PERGURUAN TINGGI PADA SMK MA'ARIF 1 SLEMAN YOGYAK - Junaidi Affan (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2011)
This study aims to determine the factors that affect the interests of continuing studies to college students of SMK Ma 'arif 1 Sleman. The factors in question is the level ofparental education, occupation ofparents, student achievement and student environment. This is a sample of students in grade 12, which amounts to 36 students. In testing variable levels of parental education, parental employment , student achievement and the environment against the interest of the college to the study used regression analysis. of these analysis tools can be known value of F and t values and the coefficient of determination. Results of the analysis showed that the value of the determinant keofisien 0.625, meaning that the interest of the students to continue their studies to college can be influenced by variable levels of parental education, occupation of parents, student achievement and the environment jointly by 62.5%, while the remaining 37.5% influenced by variables outside the study. T test results showed that the level ofparental education, student achievement and environmental partial effect on the interest to continue their studies to college. but to a variable type of work their parents do not influence significantly the interest to go to college. Variable levels ofparental education is the most dominant variables affect the interest to continue their studies to college.